2016
DOI: 10.1111/1365-2435.12671
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐evolutionary dynamics in plant–soil feedbacks

Abstract: Summary1. In the past decade, ecologists have begun to more fully appreciate the role of evolution in explaining contemporary ecological processes. Evolution is most likely to affect ecological patterns when selection pressure is particularly strong, or when the generation time of at least one interacting species is relatively short. 2. Interactions between plants and soil microbes are an excellent candidate for examining ecoevo interactions because interactions between organisms are tightly knit with the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 135 publications
(227 reference statements)
1
54
0
Order By: Relevance
“…These functional traits will likely have strong impacts on the evolution of plant interactions with their soils and vice versa (Evans et al . ; terHorst & Zee ). Continued exploration of plant function in rapidly changing environments, coupled with advances in phylogenetic comparative methods and functional evolution, will elucidate how past evolution governs future alterations of plant community composition and function induced by global change.…”
Section: Discussionmentioning
confidence: 99%
“…These functional traits will likely have strong impacts on the evolution of plant interactions with their soils and vice versa (Evans et al . ; terHorst & Zee ). Continued exploration of plant function in rapidly changing environments, coupled with advances in phylogenetic comparative methods and functional evolution, will elucidate how past evolution governs future alterations of plant community composition and function induced by global change.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not yet clear how this will affect PSF‐related processes (Bardgett et al . ) and plant evolutionary dynamics (terHorst & Zee ), it has been shown that community reordering (new genotypes or species) may have a large impact on carbon cycling and soil nutrient availability, because drought‐adapted plant species often have very different nutrient acquisition strategies (Sthultz, Gehring & Whitham ; Fischer et al . ).…”
Section: Plant–soil Feedbacks and Global Changesmentioning
confidence: 99%
“…Plant–soil systems offer many creative opportunities for testing eco‐evolutionary theory, which will provide important steps towards achieving the integration of ecosystem ecology and evolutionary biology (Bailey et al. ; Matthews et al., ; Schoener, ; terHorst & Zee, ; Van Nuland et al., ). Therefore, examining the evolutionary consequences of plant–soil linkages and feedbacks stands to significantly advance our understanding of how the interplay between ecology and evolution influences populations, structures communities and regulates many important ecosystem functions and services.…”
Section: Discussionmentioning
confidence: 99%